Children’s media of Belarus: systemdetermining factors - Kharytonоva Sviеtlana V. (Journal of the Belarusian State University. Journalism, 2020)
The article establishes the factors of development and functioning of Belarusian children’s journalism as a specific media system. The features of their influence on the system formation of Belarusian media for children’s audience in the context of the structural transformation of media for children are determined. The results of the analysis of factor relationships in the functioning of the modern children’s media system of Belarus are reflected. The author substantiates the need to update the systematic approach to the study of media for children. As a unit of media analysis, the media system was taken as a set of media that defines the channels and methods of broadcasting content, as well as forming a specific complex of structurally and functionally interconnected elements. The groups of external and internal factors that determine the dynamics of the functioning of the domestic media system for children and related to the implementation of digital information technologies in the national media system at various levels are distinguished. The correlation relationships of factors in the development of the modern children’s media system of Belarus at the macro, micro and mesoscale levels are revealed. Factor intersection and mutual influence, bilateral interaction of global and national, external and internal, subjective and objective components in the Belarusian children’s media system are studied. The interdependence of spontaneous factors and organized targeted determinants, dictated by trends in changing the information behavior of a modern children’s audience, as well as a modification of the spiritual, moral and sociocultural orientations of a digital generation of media consumers under digitalization is established. The scientific novelty of the article is to identify new scientific, methodological and practical aspects of studying the system of children’s media in Belarus, as well as the author’s disclosure of the conceptual foundations of the theory of Belarusian children’s journalism.